2018
DOI: 10.1016/j.yexmp.2018.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Different roles of FAT10, FOXO1, and ADRA2A in hepatocellular carcinoma tumorigenesis in patients with alcoholic steatohepatitis (ASH) vs non-alcoholic steatohepatitis (NASH)

Abstract: Hepatocellular carcinoma (HCC) is the fifth most common cancer and the second leading cause of cancer related deaths worldwide. Among others, non-alcoholic steatohepatitis (NASH) and alcoholic steatohepatitis (ASH) are the two major risk factors as both of them may develop cirrhosis and hepatocellular carcinoma (HCC) if left untreated. However, patients with NASH progress to HCC at a rate around 0.5% annually, while 3–10% ASH patients may progress to HCC annually. The present study is to demonstrate the molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 52 publications
2
18
0
Order By: Relevance
“…Our published data support that different molecules or pathways may be involved in NASH compared with ASH during the tumorigenesis [12,13]. We showed that the TLR/NFKB/CXCR4/7, PI3K/AKT/mTORC1, and Tec kinase signaling pathways connected with each other during MDB formation both in ASH and NASH [11][12][13][14][15][16][17][18][19][20]24].…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Our published data support that different molecules or pathways may be involved in NASH compared with ASH during the tumorigenesis [12,13]. We showed that the TLR/NFKB/CXCR4/7, PI3K/AKT/mTORC1, and Tec kinase signaling pathways connected with each other during MDB formation both in ASH and NASH [11][12][13][14][15][16][17][18][19][20]24].…”
Section: Discussionsupporting
confidence: 60%
“…Although there are many theories including genetic alterations of tumor suppressor genes, oxidative stress, and decreased liver retinoic acid level, the detailed mechanisms underlying tumorigenesis of HCC in NASH and ASH patients are not completely understood [2,9,10]. Our previous work found different gene and protein changes in ASH compared with NASH, such as the TLR/NFKB/CXCR4/7, PI3K/AKT/mTORC1 signaling pathways; Ras/RASSF1A/P53 and RUNX3/p53/GSTP1 cross links together in molecular change both in ASH and NASH [11][12][13][14][15][16][17][18][19][20]. The present study attempted to identify the role of epigenetic modulator proteins and inflammasome components in ASH and NASH patients.…”
Section: Introductionmentioning
confidence: 99%
“…FAT10 protein expression is up-regulated in ASH but not in NASH or normal controls ( Figure 2 A) which indicates the specific effect of FAT10 in ASH. These results indicate that FAT10 increased in the ASH, compared with control group, and even compared with the NASH specimens [ 41 ].…”
Section: Role Of Fat10 In Alcoholic Livermentioning
confidence: 97%
“…Using this technology, we can measure the amount of each protein in the control livers, the AH livers, and the non-alcoholic steatohepatitis (NASH) livers simultaneously, for comparison. Figure 2 shows the immunofluorescence results of the FAT10 protein, where the liver cell cytoplasm and nucleus of the hepatocytes are filled with FAT10 [41]. FAT10 is sequestered within MDBs in alcoholic steatohepatitis (ASH), suggesting that the excess expression of FAT10 in ASH is leading to the stabilization of the protein.…”
Section: Role Of Fat10 and Mdb In Human Studiesmentioning
confidence: 99%
See 1 more Smart Citation